Persisting pain in children: ensuring implementation of new guidelines. Issue 5 (12th August 2013) - Gray, Andy; Collins, John; Milani, Barbara
Abstract : The most obvious change introduced by the WHO Guidelines for the Pharmacological Treatment of Persisting Pain in Children with Medical Illness, issued in 2012, is the advocacy of a two-step rather than three-step pain 'ladder'. The guideline states that paracetamol and ibuprofen are the medicines of choice in the first step (for mild pain), and that the use of strong opioid analgesics is recommended for the relief of moderate to severe persisting pain in children with medical illnesses. The intermediate step, which dates from the 1986 and 1996 guidelines devised for adults, relied on the use of a weak opioid, notably codeine. This step is no longer advocated for children. However, there is much more than is new in the guidelines and they deserve careful consideration and deliberate action in order to ensure that children have access to the most appropriate pain relief. Hospital pharmacists are well-positioned to take a lead role in the implementation of the guidelines. They should also note the degree to which evidence to guide clinical practice is still lacking and contribute to efforts to address the priority research needs identified in the policy document.